2012
DOI: 10.1111/nmo.12015
|View full text |Cite
|
Sign up to set email alerts
|

Nestin‐expressing cells in the gut give rise to enteric neurons and glial cells

Abstract: Background Neuronal stem cells (NSCs) are promising for neurointestinal disease therapy. While NSCs have been isolated from intestinal musclularis, their presence in mucosa has not been well described. Mucosa-derived NSCs are accessible endoscopically and could be used autologously. Brain-derived Nestin-positive NSCs are important in endogenous repair and plasticity. The aim was to isolate and characterize mucosa-derived NSCs, determine their relationship to Nestin-expressing cells and demonstrate capacity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 48 publications
(77 reference statements)
3
48
0
1
Order By: Relevance
“…Immunohistochemistry was performed as previously described [40]. Cells or tissues were fixed, washed, and permeabilized with 0.1% Triton X-100 for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described [40]. Cells or tissues were fixed, washed, and permeabilized with 0.1% Triton X-100 for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of isolated ENS stem/progenitor cells from P0-Cre/EGFP mouse gut in the current study shows they express markers of neural crest (p75 and Sox10) and neural stem/progenitor cells (Nestin and Musashi1). It has been reported that Nestin positive cells in enteric ganglia of mouse and human (Azan et al 2011) form NLBs and give rise to neurons and glia in culture (Suarez-Rodriguez and BelkindGerson 2004;Belkind-Gerson et al 2013). Musashi1, a well-known marker for stem cells in nervous system (Sakakibara et al 1996;Okano et al 2002) and intestine (Potten et al 2003), plays a key role in maintaining undifferentiated status of neural stem cells (Okano et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These cells can give rise to neurons and glial cells when grafted into explants of chick, mouse or human gut (Mosher et al 2007;Metzger et al 2009;Lindley et al 2008;Belkind-Gerson et al 2013) or postnatal mouse gut in vivo (Hotta et al 2013). Moreover, a recent human study has shown that enteric neuronal stem/progenitor cells can be obtained from mucosal biopsy specimens taken during routine endoscopy from children with Hirschsprung's disease (Metzger et al 2009), demonstrating the potential for the use of patient-derived cells in the future for autologous cell replacement that circumvent ethical and immunological challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Well-established protocols have been developed to isolate enteric NPCs from the GI tract [21,22]. When transplanted into rodents, these cells differentiated into neurons that reestablished motility or function [23,24].…”
Section: Discussionmentioning
confidence: 99%